Would midpalatal suture characteristics help to predict the success rate of miniscrew-assisted rapid palatal expansion? - Jesus, Adriana Souza de [UNESP]; Oliveira, Cibele Braga de [UNESP]; Murata, Wilson Humio; Suzuki, Selly Sayuri; Santos-Pinto, Ary dos [UNESP] (Elsevier, 2021)
Introduction: The objective of this study was to evaluate whether the success or failure of miniscrew-assisted rapid palatal expansion (MARPE) in patients with advanced bone maturation could be related to factors such as midpalatal suture density (MPSD), midpalatal maturation stage (MPSM), midpalatal bone thickness (MBTh), palatal length (PL), expander screw position (ESP), and patient's age. Methods: Cone-beam computed tomography scans of 25 patients of both sexes, aged 15-37 years (23 ± 7.2), presenting transverse maxillary deficiency and complete skeletal maturation (cervical vertebral maturation stage 5) treated using MARPE were evaluated. The success of MARPE was confirmed by the midpalatal suture opening and failure when no opening or limited separation of midpalatal suture occurred. Data were analyzed using t test for independent samples for differences in the variables of success and failure cases and the Pearson correlation test to evaluate the relation of the success and age, ESP, MPSD, MPSM, PL, and MBTh. Results: Age, MPSM, and MBTh at 12 mm and 16 mm presented statistically significant results (P <0.05). The older the patient with advanced bone maturation, the lower the success rates of MARPE (94.1%, 90%, and 76% for 25, 30, and 37 years, respectively). The ESP had similar averages in cases of success (15.34 mm) and failure (13.51 mm). There was no correlation between ESP, MPSD, MPSM, or PL and MARPE success. Conclusions: MARPE success was related to age and a greater MBTh at 12 mm and 16 mm.